The Impact of Educational Games on Learning:Systematic Review of Literature and Field Studies - Saefudin Zuhri; Sholeh Hidayat; Fadlullah Fadlullah; Syammali Adam (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
Educational games in learning have a high interest among students, stimulating motivation and student involvement. This research aims to provide a summary of empirical findings from the latest literature in the field of gamification, which is currently developing in the learning domain. The study also uncovers cutting-edge scientific evidence on the development of emerging learning technologies and gamification plugins, as well as exploring the potential future directions of research in revolutionizing learning through gamification. A systematic literature review that combines thematic and content analysis of 46 empirical research papers published in the Scopus database between 2020 and 2024. This study provides an in-depth assessment and evaluation of the various contradictions found in the literature, setting the stage for future research studies to re-examine the theoretical underpinnings of gamification, its methodological approaches, theoretical models, game and platform applications, educational game mechanisms, and learning outcomes. This study not only attempts to explain the novelty of game-based learning, which is considered a game-changer and a key driver of learning motivation and user experience, but also seeks to outline the main challenges and obstacles of educational gaming. Keywords: Gamification, Learning, Literature Review